Нанолазерна дезінфекція системи кореневого каналу зуба - Бариляк, А.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
A nanolaser method of the disinfection root canal system of tooth is offered. Comparing the bactericidal action of silver nanoparticles to the bactericidal effect of laser irradiation in the root canal of tooth in vitro is conducted. The increase of the depth of penetration of nanoparticles is set in dentinal tubulie at the nanosecond sentinel mode of irradiation. Bacteriological information of researches confirmed that an additional laser irradiation at a wavelength of 1064 nm deeply enough got to the dentinal structures as a result of the waveguide effect and, in combination with silver nanoparticles provides a synergistic effect - total elimination of bacteria is due to the additional photoactivation of nanoparticles.